Memorandum of understanding between Universiti Teknologi MARA and RS Advanced Technology Sdn. Bhd. / Fakulti Kejuruteraan Mekanikal - Universiti Teknologi MARA, Fakulti Kejuruteraan Mekanikal (Universiti Teknologi MARA (UiTM), 2019)
Memorandum of understanding on university-industry joint collaboration and partnership for research and development on advanced ceramic and metal powder parts manufacturing technology.